Developing a Communication Curriculum and Workshop for an Internal Medicine Residency Program. Issue 6 (June 2015) - Salib, Sherine; Glowacki, Elizabeth M.; Chilek, Lindsay A.; Mackert, Michael
<x xml:space="preserve">Abstract</x> Objectives Learning effective communication is essential for physicians. Effective communication has been shown to affect healthcare outcomes, including patient safety, adherence rates, patient satisfaction, and enhanced teamwork. The importance of these skills has become even more apparent in recent years, with value-based purchasing programs and federal measures of patient satisfaction in the form of Hospital Consumer Assessment of Healthcare Providers and Systems scores becoming an important part of measuring the performance of a healthcare facility. Methods We conducted a communication workshop for internal medicine residents at the University of Texas. Topics covered included the Acknowledge, Introduce, Duration, Explanation, Thank You framework; managing up; resolving conflicts; error disclosure; new medication and discharge counseling; intercultural communication; understanding Hospital Consumer Assessment of Healthcare Providers and Systems scores; and avoiding burnout. Because it would have been logistically difficult to block whole days for the workshop, the various topics were offered to residents during their regular noon conference hour for several consecutive days. After the workshop, the residents completed an anonymous questionnaire regarding their perception of the importance of various aspects of communication in patient care. Results The majority of the participating residents perceived the various communication skills explored during the workshop to be highly important in patient care. Concurrently, however, most residents believed that they had initially overestimated their knowledge about these various communication issues. Some demographic differences in the responses also were noted. Conclusions Our findings demonstrate a needs gap and an area of potential improvement in medical education. We anticipate that with the growing understanding of the importance of communication skills in the healthcare setting, there will be an enhanced role for teaching these skills at all levels of medical education. More studies are needed to further elucidate the specific areas of communication in health care where additional training is necessary.